Kesesuaian Mekanisme Pembiayaan Murabahah Produk KPR Menurut Fatwa DSN MUI Di Bank JATIM Syariah Surabaya Cabang Darmo - Dara Setianti Kania P; Siti Inayatul Faizah (Universitas Airlangga, 2016)
This research aims to determine how the suitability of handling Murabaha financing problem house loan product at fatwa of the National Sharia Supervisory Board of the Indonesian Ulama Council (DSN-MUI) in Bank Jatim Sharia Surabaya. The object of the study are Bank Jatim Sharia’s competent employees which competent in murabaha financing. This study used qualitative descriptive approach. The researcher collected the data by interviewing three employees of Bank Jatim Sharia.This research finds that the six points which used as references in the study such as price, advance, fine, guarantee, and collectability murabaha financing of House Loan product are suitable with fatwa of the National Sharia Supervisory Board of the Indonesian Ulama Council (DSN-MUI). But, there is one which doesn’t suitable with fatwa.